1980
DOI: 10.1080/15298668091424465
|View full text |Cite
|
Sign up to set email alerts
|

Detection of mercury in air in the presence of chlorine and water vapor

Abstract: Evidence is presented that low concentrations of mercury and chlorine vapor in air form reaction products. At constant mercury concentration the rate of formation increases with chlorine concentration and relative humidity. The mercury-chlorine compound as well as the vapor of elemental mercury are absorbed by Hopcalite or by KMnO4-H2SO4 scrubber solution. The compound can be separated from mercury vapor by its absorption in polyurethane or by filtration by means of Millipore aerosol membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This trend is similar to the Cl 2 + Hg 0 (g) data of Menke and Wallis. 16 In the previous study of reaction 1 by Hall, 20 there was evidence for heterogeneous ozone chemistry. Hall found the rate of Hg 0 (g) loss was equal to k net [Hg 0 (g)][O 3 ] b , where b = 0.81.…”
Section: Kinetic Results and Potential Mechanismsmentioning
confidence: 93%
See 1 more Smart Citation
“…This trend is similar to the Cl 2 + Hg 0 (g) data of Menke and Wallis. 16 In the previous study of reaction 1 by Hall, 20 there was evidence for heterogeneous ozone chemistry. Hall found the rate of Hg 0 (g) loss was equal to k net [Hg 0 (g)][O 3 ] b , where b = 0.81.…”
Section: Kinetic Results and Potential Mechanismsmentioning
confidence: 93%
“…Among these oxidants considered, ozone was regarded as the among the most important mercury-depleting compounds in the troposphere outside marine or polar regions. 1 Previous studies have shown that the apparent rate constant for the oxidation of Hg 0 (g) can be increased if water is present; Menke and Wallis 16 found the rate of mercury oxidation by chlorine will triple when increasing RH to 80%. A later study by Lindqvist and Iverfeldt 17 observed that the presence of liquid water and ozone together will enhance deposition of Hg 0 (g).…”
Section: Introductionmentioning
confidence: 99%
“…For various concentrations of Hg 0 (g) and Cl2(g) ,rate constants of 9.8-5010 -18 cm 3 molecules -1 s -1 1have been reported (Sumner et al, 2005). Earlier kinetic studies (Medhekaret al, 1979;Menke and Wallis, 1980;Schroeder et al, 1991;Seignuer et al, 1994;Skare and Hohansson, 1992;Sliger et al,2000) yielded rate…”
Section: A14 Reaction With Cl2(g) Br2(g) I2(g) and F2(g)mentioning
confidence: 95%
“…Our findings below are in agreement with the results of Fontijn and Hranisavljevic. Using Menke and Wallis' experimental results, 18 Schroeder et al 21 calculated a rate constant, providing an upper limit of 2.4 × 10 8 cm 3 mol −1 s −1 . However, they stated that the actual reaction is not entirely described by Hg + Cl 2 → HgCl 2 .…”
Section: ■ Introductionmentioning
confidence: 99%